HUBUNGAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TIM PEMBINA LBD (LOCAL BUSINESS DEVELOPMENT) DENGAN SIKAP TERHADAP PELATIHAN LBD - Yuliza, Efa (STAI Hubbulwathan Duri, 2016)
Attitude is a component that consists of cognitive, affective and psychomotor. Formation and attitude change is determined by internal and external factors of the individual. One of the external factors that influence the attitudes of participants towards the training LBD is a transformational leadership style LBD team builder. Transformational leadership style is the way shown by superiors to subordinates within the framework of the provision of information through the encouragement and support. Support subordinates to think of new and better ways of working, caring, and emphasized the importance of values and beliefs in influencing subordinates. This paper aimed to explore the relationship between transformational leadership of LBD team (Local Business Development) with the attitude to training LBD and the LBD participants who are around the area of operation of PT. CPI, Bengkalis.